Usefulness and metabolic implications of a 60-second repeated jumps test as a predictor of acrobatic jumping performance in gymnasts - Marina, M.; Rodriguez, F. A. (Biology of Sport, 2013)
Gymnastics floor exercises are composed of a set of four to five successive acrobatic jumps usually called a "series". The aims of the study were: 1) to relate the acrobatic gymnastics performance of these series with a repeated jumps test of similar duration (R60), 2) to study the relation between R60 and physiological parameters (heart rate and blood lactate), and the performance obtained in different kinds of jumps, 3) to confirm whether R60, executed without a damped jumping technique, can be considered an anaerobic lactic power test. Twenty male and twenty-four female gymnasts performed three repeated jumps tests for 5 s (R5), 10 s (R10) and 60 s (R60) and vertical jumps, such as drop jumps (DJ), squat jumps (SJ) and countermovement jumps (CMJ). We assessed heart rate (HR) and blood lactate during R10 and R60. The average values of the maximal blood lactate concentration (Lmax) after R10 (males = 2.5±0.6 mmol · l-1; females = 2.1±0.8 mmol · l-1) confirm that anaerobic glycolysis is not activated to a high level. In R60, the Lmax (males = 7.5±1.7 mmol · l-1; females = 5.9±2.1 mmol · l-1) that was recorded does not validate R60 as an anaerobic lactic power test. We confirmed the relation between the average power obtained in R60 (R60Wm) and the acrobatic performance on the floor. The inclusion in the multiple regression equation of the best power in DJ and the best flight-contact ratio (FC) in R5 confirms the influence of other non-metabolic components on the variability in R60 performance, at least in gymnasts.